2022
DOI: 10.1097/md.0000000000032270
|View full text |Cite
|
Sign up to set email alerts
|

Thunder-fire moxibustion for lumbar disc herniation: A systematic review and meta-analysis

Abstract: Background: Lumbar disc herniation (LDH) is a common degenerative disease that severely impacts the quality of life of patients. Thunder-fire moxibustion is an ancient Chinese medicine-based external therapeutic procedure that has been employed for pain relief until this day. The focus of our study was to demonstrate the effectiveness and safety of thunder-fire moxibustion in the treatment of LDH.Methods: The literature databases searched included the Cochrane Library, Web of Science, Springer, PubMed, Wanfang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…A meta-analysis included 17 studies, with a total of 1344 such patients, and analyzed the efficacy of lightning fire moxibustion on this disease. The results showed that compared with other therapies, lightning fire moxibustion significantly improved the effective rate, with a significant clinical effect, which was 20% higher, with a statistically significant difference [8].…”
Section: Acupuncture and Moxibustion Treatmentmentioning
confidence: 90%
“…A meta-analysis included 17 studies, with a total of 1344 such patients, and analyzed the efficacy of lightning fire moxibustion on this disease. The results showed that compared with other therapies, lightning fire moxibustion significantly improved the effective rate, with a significant clinical effect, which was 20% higher, with a statistically significant difference [8].…”
Section: Acupuncture and Moxibustion Treatmentmentioning
confidence: 90%